Mental Burden of Hospital Workers During the COVID-19 Crisis: A Quanti-Qualitative Analysis - Luquiens, Amandine; Morales, Jennifer; Bonneville, Marion; Potier, Hugo; Perney, Pascal; Faure, Gilles; Canaguier, Astrid (Frontiers in Psychiatry, 2021)
Abstract Context This study is a quanti-qualitative analysis of all contacts to a helpline service for hospital workers during the COVID-19 crisis. Our aim was to describe the nature of mental burden in hospital workers and factors subjectively associated to this burden in the workers’ perspective. Methods We included all 50 contacts from 25 different workers and 10 different professions during one month. We described the corpus and reported the computerized qualitative analysis of summary of contacts. We performed a descendant hierarchical analysis and analyzed specificities of classes of age with a correspondence factor analysis. Results The corpus was composed of 3 classes: (1) distress specific to the COVID-19 situation, (2) help provided, (3) pre-existing psychological vulnerability. Factors subjectively responsible for mental distress were: (a) the contamination risk (b) confinement (c) rapidly evolving situation and changing instructions. Lack of “COVID-free time” seemed to increase negative emotions. Reassignment to high viral density unit was a stressor especially in older workers. Young workers mentioned pre-existing vulnerability more than others. Fear of death was shared by all classes of age disregarding the objective risk of contamination. Discussion Hospital workers cumulate mental distress factors common with the general population and specific to the hospital environment. Preserving and organize support for mental health of all hospital workers is a critical challenge, including those with poorly recognized professions. Leads for institutions to avoid additional stressors for hospital workers are presented. Young workers with pre-existing vulnerability seem particularly impacted.